Molecular Characterization and Clinical Characteristics of m5C-Based RNA Methylation in Spinal Cord Injury: Validated by qPCR - Liang Cao; Wen Jun Pi; Qiang Zhang; Qing Li (International Journal of Genomics)
Aberrant patterns of 5-methylcytosine (m5C)-based ribonucleic acid (RNA) methylation have critical roles in various human diseases, but their importance in spinal cord injury (SCI) is largely unknown. We explore the expression patterns and potential roles of m5C-based regulators of RNA modification after SCI. We analyzed 16 m5C-based regulators of RNA modification in tissues with SCI and normal rats from the Gene Expression Omnibus database. We constructed a “gene signature” of m5C-based regulators of RNA modification to predict the prognosis of SCI using least absolute shrinkage and selection operator regression and random-forest strategy. We found that the m5C-related genes, deoxyribonucleic acid (DNA) methyltransferase1 (Dnmt1), methyl-CpG binding domain protein 2 (Mbd2), ubiquitin-like with PHD and ring finger domains 1 (Uhrf1), uracil-N-glycosylase (Ung), and zinc finger and BTB(brica-brac, tramtrack, and broad) domain containing 38 (Zbtb38) had high expression, and zinc finger and BTB domain containing 4 (Zbtb4) had low expression in SCI. Analysis of the correlation between the gene sets of m5C-based regulators of RNA modification and immune-cell infiltration and immune response revealed Dnmt1, DNA methyltransferases 3A (Dnmt3a), Mbd2, and Ung to be positive regulators of the immune microenvironment, and Zbtb4 may negatively regulate the immune environment. Then, two molecular subtypes were identified based on 16 m5C-regulated genes. Functional-enrichment analysis of differentially expressed genes between different patterns of m5C-based modification was undertaken. Through the creation of a protein–protein interaction network, we screened 11 hub genes. We demonstrated their importance between SCI group and sham group using real-time reverse transcription-quantitative polymerase chain reaction in rat model. Expression of hub genes did not correlate with mitophagy but was positively correlated with endoplasmic reticulum stress (ERS), which suggested that there may be differences in ERS between different patterns of m5C-based modification. This present study explored and discovered the close link between m5C regulators-related genes and SCI. We also hope our findings may contribute to further mechanistic and therapeutic research on the role of key m5C regulators after SCI.